A black energy-saving electrochromic device based on a dye copolymer–metal complex. Issue 47 (24th November 2022) - Shen, Ruipeng; Xi, Haozhe; Wang, Yuyang; Ren, Guozhu; Liu, Duo; Zhang, Yu-Mo; Zhang, Sean Xiao-An
Abstract : A dye copolymer–metal complex with bistable black electrochromic property has been synthesized. The compatibility of different components has been optimized, which brings device satisfying bistability, contrast ratio and cyclic reversibility. Abstract : Bistable black electrochromic (EC) devices have attracted increasing attention of researchers due to their ultra-low energy consumption and tunable sunlight penetration in the visible region. However, unsatisfactory optical performance and color stability limit their development and application in smart windows and non-emissive displays. In this work, aiming at the problems of poor dynamic coordination, and insufficient stability between copper ions and dye molecules, a copolymer containing a dye and cuprous complex has been designed and synthesized for a black bistable EC material with energy-saving properties. Based on this, a semi-solid black EC prototype device with bistable ability (maintains the color state for 2 h after electric stimulation) and high contrast ratio has been fabricated and demonstrated. The method proposed and verified here is applicable to other dye molecules with similar functional groups, thereby realizing energy-saving and multicolor display.